Phytochemical Screening Of Ethanol Extract Of Temu Kunci (Boesenbergia Rotunda (L.) Mansf) Rhizome Extract And Testing Of Bilirubin Levels In Male White Mice - Harahap, Mawandha Sari; Harahap, Urip; Sitorus, Panal (Publisher Cv. Inara, 2023)
Liver Disease Is A Deadly Disease That Has Attacked Many People. Liver Disease Is A Disease That Occurs As A Result Of An Unhealthy Lifestyle. Usually, The Patient Will Consume Drugs With Chemical Compounds To Overcome The Problem Of This Disease. The Long-Term Use Of Chemical Drugs Will Certainly Cause Side Effects Or, Even Worse, Cause New Diseases. Therefore, The Latest Treatment Methods Must Be Developed To Minimize Side Effects, Namely The Use Of Traditional Medicines. The Purpose Of This Study Was To Determine The Use Of Temu Kunci Rhizome As An Alternative To Reduce Total Bilirubin Levels In Rats As Experimental Animals. This Study Used Rats As Experimental Animals, Which Were Divided Into 6 Test Groups, Namely Group 1 Without Treatment, Group 2 With 0.5% CMC Suspension, Group 3 With 200 Mg Acetylcysteine, Group 4 With 250 Mg/Kg BW Ethanol Extract Of Temukunci, Group 5 Treated With A 500 Mg/Kg BW Dose Of Ethanol Extract Of Temukunci, And Group 6 With A 750 Mg/Kg BW Ethanol Extract Of Temukunci. From The Results Of The Research Conducted, The Ethanol Extract Of Temu Kunci At A Dose Of 750 Mg/Kg BW Was The Best Treatment For Reducing Total Bilirubin Levels In Rats As Experimental Animals.